2008
DOI: 10.1508/cytologia.73.213
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and Cytogenetic Study in F1 and F2 of Interspecific Cross between Gossypium arboreum*Gossypium anomalum

Abstract: Summary An interspecific hybrid between G. arboreumϫG. anomalum was obtained by pollinating previous day bagged flowers of G. arboreum genetic male sterile line MPKV GMS with pollen from wild G. anomalum.The chromosome constitution in all the plants of G. arboreum and G. anomalum were found to be normal while interspecific hybrid showed mean chromosome association 1.081 I ϩ10.479 II ϩ0.000 III ϩ0.990 IV with normal sporads. Interspecific hybrid showed anomalous behavior of univalent and formation of single and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Chromosomal crossing over during meiosis and loss of primer attachment pair sites could be another reason for producing novel allelic patterns in genotypes (Sheidai et al, 2008). This phenomenon has also been reported in other plant species hybrids (Smith et al, 1996;Sushir et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…Chromosomal crossing over during meiosis and loss of primer attachment pair sites could be another reason for producing novel allelic patterns in genotypes (Sheidai et al, 2008). This phenomenon has also been reported in other plant species hybrids (Smith et al, 1996;Sushir et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…Dendrogram resulting from UPGMA cluster and POC plot based on RAPD data from control, 1 mT for 1 h, 7 mT for 3 h in canola. or rearrangement of some nucleotides (Sushir et al 2008). Our previous work showed a significant difference of meiotic characters in EMF pretreated plants as compared to control.…”
Section: Discussionmentioning
confidence: 73%
“…Chromosomal crossing over during meiosis may result in loss of primer attachment pair sites in the offspring leading to novel ISSR pattern in the offspring (Smith et al, 1996). Sushir et al (2008) carried out cytogenetic and RAPD analysis of F 1 and F 2 progenies of the interspecific cross between Gossypium arboretum X G. anomalum and reported that among nine F 2 segregates, F 2 to 1 progeny plants showed one additional band than F 1 and F 2 to 5 progeny plant showed the recombination event. On the contrary in plants F 2 to 6 and F 2 to 8 loss of priming sites happened showing that recombination between A and B genomes of G. arboreum and G. anomalum respectively is possible (Sushir et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sushir et al (2008) carried out cytogenetic and RAPD analysis of F 1 and F 2 progenies of the interspecific cross between Gossypium arboretum X G. anomalum and reported that among nine F 2 segregates, F 2 to 1 progeny plants showed one additional band than F 1 and F 2 to 5 progeny plant showed the recombination event. On the contrary in plants F 2 to 6 and F 2 to 8 loss of priming sites happened showing that recombination between A and B genomes of G. arboreum and G. anomalum respectively is possible (Sushir et al, 2008). Sheidai et al (2008) also used RAPD markers to analyse different cotton genotypes and reported the occurrence of novel RAPD bands in the hybrids not observed in their parents and also reported the absence of RAPD bands in the hybrids which were present in their parents.…”
Section: Discussionmentioning
confidence: 99%